Iron-deficiency Anemia in Children with Febrile Seizure: A Case-Control Study - GHASEMI, Fateme (Shahid Beheshti University of Medical Sciences, 2014)
OBJECTIVE: Considering the recurrence of febrile seizure and costs for families, many studies have attempted to identify its risk factors. Some recent studies have reported that anemia is more common in children with febrile convulsion, whereas others have reported that iron deficiency raises the seizure threshold. This study was done to compare iron-deficiency anemia in children with first FS with children having febrile illness alone and with healthy children. MATERIALS & METHODS: This case-control study evaluated 300 children in three groups (first FS, febrile without convulsion, and healthy) in Khoramabad Madani Hospital from September 2009 to September 2010. Body temperature on admission was measured using the tympanic method. CBC diff, MCV, MCH, MCHC, serum iron, plasma ferritin and TIBC tests were performed for all participants. Data were analyzed by frequency, mean, standard deviation, ANOVA, and chi-square statistical tests. Odds ratios were estimated by logistic regression at a confidence level of 95%. RESULTS: Forty percent of the cases with FS had iron-deficiency anemia, compared to 26% of children with febrile illness without seizure and 12% of healthy children. The Odds ratio for iron-deficiency anemia in the patients with FS was 1.89 (95% CI, 1.04-5.17) compared to the febrile children without convulsion and 2.21 (95% CI, 1.54-3.46) compared to the healthy group. CONCLUSION: Children with FS are more likely to be iron-deficient than those with febrile illness alone and healthy children. Thus, iron-deficiency anemia could be a risk factor for FS.